Fetal sex and maternal risk of pre‐eclampsia/eclampsia: a systematic review and meta‐analysis. (17th June 2016) - Jaskolka, D; Retnakaran, R; Zinman, B; Kramer, CK
Abstract : Background: A preponderance of male fetuses in pregnancies complicated by pre‐eclampsia was described over 40 years ago. Since then, however, there has been conflicting evidence in the literature, with some studies supporting a male preponderance, some demonstrating no relationship with fetal sex, and others reporting increased risk in pregnancies bearing females. Objectives: In this context, we sought to conduct a systematic review and meta‐analysis to objectively evaluate the relationship between fetal sex and maternal risk of pre‐eclampsia/eclampsia. Search strategy: Studies from January 1950 to April 2015 were identified from PUBMED and EMBASE. Selection criteria: This systematic review and meta‐analysis evaluated 22 articles reporting data on fetal sex and prevalence of pre‐eclampsia/eclampsia. Data collection and analysis: Data were extracted by two independent reviewers. Pooled estimates of the relative risk (RR) were calculated by random‐effects model. Main results: Male fetus was considered the exposure and prevalence of maternal pre‐eclampsia/eclampsia was the outcome of interest. We identified 534 studies through electronic searches and three studies through manual searches. Twenty‐two studies fulfilled the inclusion criteria, yielding data on 3 163 735 women. Pooled analyses of these studies showed no association between male fetal sex and maternal risk of pre‐eclampsia/eclampsia (RR 1.01; 95% confidence interval, 95% CI 0.97–1.05); however, a subgroup analysis including only studies that evaluated the non‐Asian population ( n = 2 931 771 women) demonstrated that male fetal sex was associated with increased maternal risk of pre‐eclampsia/eclampsia (RR 1.05; 95% CI 1.03–1.06; I 2 = 10%; P = 0.33). Conclusion: Male fetal sex is associated with maternal risk of pre‐eclampsia/eclampsia in the non‐Asian population. Tweetable abstract: Fetal sex is associated with maternal risk of pre‐eclampsia/eclampsia in the non‐Asian population. Abstract : Tweetable abstract Fetal sex is associated with maternal risk of pre‐eclampsia/eclampsia in the non‐Asian population.